Critical issues and needs in management of primary immunodeficiency diseases in Latin America (2011)
ABSTRACT: Experts from six Latin American countries met to discuss critical issues and needs in the diagnosis and management of primary immunodeficiency diseases (PIDD). The diagnosis of PIDD is generally made following referral to an immunology centre located in a major city, but many paediatricians and general practitioners are not sufficiently trained to suspect PIDD in the first place. Access to laboratory testing is generally limited, and only some screening tests are typically covered by government health programmes. Specialised diagnostic tests are generally not reimbursed. Access to treatment varies by country reflecting differences in healthcare systems and reimbursement policies. An online PIDD Registry Programme for Latin America has been available since 2009, which will provide information about PIDD epidemiology in the region. Additional collaboration across countries appears feasible in at least two areas: a laboratory network to facilitate the diagnosis of PIDD, and educational programmes to improve PIDD awareness. In total, these collaborations should make it possible to advance the diagnosis and management of PIDD in Latin America.